A Rich Source of Amino Acids: Crotalaria juncea Seed - Yadav, R.N.; Thakur, Vibha (Asian Journal of Chemistry, 2010)
The present paper deals with the isolation and identification of Various amino acids form the seeds of Crotalaria juncea.